A systematic review of serum autoantibodies as biomarkers for pancreatic cancer detection - Dumstrei, Karin; Chen, Hongda; Brenner, Hermann (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7098 Karin Dumstrei, Hongda Chen, Hermann Brenner
Gesehen am 21.02.2020